Penyederhanaan Birokrasi : Wujud Nyata Langkah Pemerintah Indonesia Menuju Agile Governance - Suryani, Eny; Diniawaty, Shintya Awalin (Jurnal Publik, 2024)
This research aims to find out the steps taken by the Government of Indonesia in implementing, maintaining, and developing Agile Governance. This research is a type of qualitative research and uses a literature study approach, which comes from primary data and secondary data through several articles published from 2019 to 2024, totalling 58 articles. The results of the discussion in implementing, maintaining, and developing Agile Governance in the Government of Indonesia must pay attention to factors such as transparent performance appraisal, development of individuals who continue to learn, and organisational adaptation through the 4R model (Reframing, Restructuring, Revitalisation, and Renewal) to achieve the goals of bureaucratic reform and strengthen government organisations.